How China's rise is changing the Middle East - Ehteshami, Anoushiravan; Horesh, Niv (London ; New York, NY : Routledge/Taylor & Francis Group, 2020)
This book explores the extent to which China's rise is changing the economic, security, political and social-cultural aspects of the Middle East - a region of significant strategic importance to the West and of increasing importance to the East. With its growing dependence on Middle East oil and gas, China has more at stake in this region than any other Asian power and, not surprisingly, has begun increasing its engagement with the region, with profound implications for other stakeholders. The book charts the history of China's links with the Middle East, discusses China's involvement with each of the major countries of the region, considers how China's rise is reshaping Middle Easterners' perceptions of China and the Chinese people and examines the very latest developments.
The Chinese-Middle Eastern encounter in broader historical perspective : from the Han to the Qing dynasty -- China's presence in the Middle East in the long 20th century, 1912-2012 -- Eyeing military alliance : Sino-Iranian mutual strategic perceptions leading onto the Trump era -- Chinese strategic perceptions of Saudi Arabia -- A model for self-development : Egyptian perceptions of China since 2012 -- Our "new best friend" : Turkish perceptions of China since 2012 -- The PRC's slowly improving relations with Israel.
Includes bibliographical references and index.
Keywords: China -- Foreign relations -- Middle East; Middle East -- Foreign relations -- China; China -- Foreign economic relations -- Middle East; Middle East -- Foreign economic relations -- China